ANALYSIS OF THE PRACTICALITY AND EFFECTIVENESS OF ANDROID-BASED SIGN LANGUAGE RECOGNITION LEARNING MEDIA IN AN EXCEPTIONAL SCHOOL - Faisal, Faisal; Tjandi, Yunus; Jaya, Hendra (Jurnal Vokasi Keteknikan, 2025)
The purpose of this study is to analyze the practicality and effectiveness of android-based sign language recognition learning media applications as an alternative to learning media in extraordinary schools (SLB). This type of research is Research and Development (R&D) with the Concurrent Triangulation design combination method.The subjects of the study were 20 sign language teachers from three SLB schools in the cities of Makassar and Gowa as well as application users who assessed the practicality and effectiveness of the learning media applications that they would teach to deaf students. The data collection technique consists of observation, interviews, literature studies and the distribution of questionnaires/questionnaires. Meanwhile, the instruments used include observation sheets, interview sheets and questionnaire/questionnaire sheets. There are 10 criteria data components to assess the practicality of learning media applications and 15 criteria data components to assess the effectiveness of learning media applications. The results showed that the level of practicality of learning media was 3.65 while the effectiveness level of learning media was 3.41. By using the Likert scale, it can be concluded that android-based sign language recognition learning media applications are very practical and very effective for teachers to use as an alternative to sign language recognition learning media in SLB.